Depletion of myeloid cells exacerbates hepatitis and induces an aberrant increase in histone H3 in mouse serum. Issue 1 (25th November 2016) - Piao, Xuehua; Yamazaki, Soh; Komazawa‐Sakon, Sachiko; Miyake, Sanae; Nakabayashi, Osamu; Kurosawa, Takeyuki; Mikami, Tetsuo; Tanaka, Minoru; Van Rooijen, Nico; Ohmuraya, Masaki; Oikawa, Akira; Kojima, Yuko; et al.
Abstract : Tissue‐resident macrophages and bone marrow (BM)‐derived monocytes play a crucial role in the maintenance of tissue homeostasis; however, their contribution to recovery from acute tissue injury is not fully understood. To address this issue, we generated an acute murine liver injury model using hepatocyte‐specific Cflar ‐deficient ( Cflar Hep‐low ) mice. Cellular FLICE‐inhibitory protein expression was down‐regulated in Cflar ‐deficient hepatocytes, which thereby increased susceptibility of hepatocytes to death receptor–induced apoptosis. Cflar Hep‐low mice developed acute hepatitis and recovered with clearance of apoptotic hepatocytes at 24 hours after injection of low doses of tumor necrosis factor α (TNFα), which could not induce hepatitis in wild‐type (WT) mice. Depletion of Kupffer cells (KCs) by clodronate liposomes did not impair clearance of dying hepatocytes or exacerbate hepatitis in Cflar Hep‐low mice. To elucidate the roles of BM‐derived monocytes and neutrophils in clearance of apoptotic hepatocytes, we examined the effect of depletion of these cells on TNFα‐induced hepatitis in Cflar Hep‐low mice. We reconstituted Cflar Hep‐low mice with BM cells from transgenic mice in which human diphtheria toxin receptor ( DTR ) was expressed under control of the lysozyme M ( LysM ) promoter. TNFα‐induced infiltration of myeloid cells, including monocytes and neutrophils, was completely ablated in LysM‐DTR BM‐reconstituted Cflar Hep‐low mice pretreated with diphtheria toxin, whereas KCs remained present in the livers. Under these experimental conditions, LysM‐DTR BM‐reconstituted Cflar Hep‐low mice rapidly developed severe hepatitis and succumbed within several hours of TNFα injection. We found that serum interleukin‐6 (IL‐6), TNFα, and histone H3 were aberrantly increased in LysM‐DTR BM‐reconstituted, but not in WT BM‐reconstituted, Cflar Hep‐low mice following TNFα injection. Conclusion : These findings indicate an unexpected role of myeloid cells in decreasing serum IL‐6, TNFα, and histone H3 levels via the suppression of TNFα‐induced hepatocyte apoptosis. (Hepatology 2017;65:237‐252).